Effect of hormone therapy on postural balance in postmenopausal women - Cesar Rodrigues Barral, Ana Beatriz [UNESP]; Nahás, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge [UNESP]; Cangussu, Luciana Mendes [UNESP]; Buttros, Davi de Araujo [UNESP] (Lippincott Williams & Wilkins, 2012)
Objective: The aim of this study was to analyze the effects of hormone therapy (HT) on postural balance in postmenopausal women and its association with risk of falls.Methods: In this cross-sectional study, a total of 225 Brazilian postmenopausal women aged 45 to 75 years were included and divided into two groups: HT users (n = 102) and nonusers (n = 123). HT users were women who had continuously taken HT throughout the preceding 6 months, whereas nonusers received no such therapy during the same period. Women with amenorrhea for more than 12 months and aged 45 years or older were included. Those with neurological or musculoskeletal disorders, vestibulopathies, uncorrected visual deficit, or drug use that could affect balance were excluded. Histories of falls (previous 24 mo) as well as clinical and anthropometric characteristics were analyzed. Postural balance was assessed through stabilometry (computerized force platform), Romberg test, and crouching test. Statistical analysis included the median test, chi(2) test, Spearman correlation coefficient, and logistic regression method (odds ratio).Results: Women users of HT were younger (53.0 vs 57.0 y) and with a shorter time since menopause (5.5 vs 10.0 y) than nonusers (P < 0.05). No anthropometric differences were observed. The number of women who had experienced falls was significantly lower among HT users than nonusers: 51 vs 88 falls, respectively (P < 0.05), and presented an adjusted risk of falls of 0.49 (95% CI, 0.27-0.88) times lower than the nonusers group. For the stabilometric parameters, HT users showed significantly lower amplitude in body oscillation (latero-lateral and antero-posterior) and a smaller oscillation area compared with nonusers (P < 0.05). There was no significant correlation between the Romberg test and fall rate (P > 0.05). In the crouching test, 47.1% of the participants showed an adequate level of muscle strength in lower limbs without differences between the groups (P > 0.05).Conclusions: Postmenopausal women using HT showed lower frequency of falls and a better performance in stabilometric parameters than did nonusers.
Keywords: Menopause; Hormone therapy; Postural balance; Falls